Surface potential modeling of dual metal gate-graded channel-dual oxide thickness with two dielectric constant different of surrounding gate MOSFET - Hind Jaafar; Abdellah Aouaj; A. Bouziane; Benjamin Iñiguez (International Journal of Reconfigurable and Embedded Systems (IJRES), 2020)
An Analytical study for the surface potential, threshold voltage and Subthreshold swing (SS) of Dual-metal Gate Graded channel and Dual Oxide Thickness with two dielectric constant different cylindrical gate surrounding-gate (DMG-GC-DOTTDCD) metal–oxide–semiconductor field-effect transistors (MOSFETs) is proposed to investigate short-channel effects (SCEs). The performance of the modified structure was studied by developing physics-based analytical models for the surface potential, threshold voltage shift, and Subthreshold swing. It is shown that the novel MOSFET could significantly reduce threshold voltage shift and Subthreshold swing, can also provides improved electron transport and reduced short channel effects (SCE). Results reveal that the DMG-GC-DOTTDCD devices with different dielectric constant offer superior characteristics as compared to DMG-GC-DOT devices. The derived analytical models agree well with simulation by ATLAS.